2004
DOI: 10.1021/ci049842y
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of π-Electrons in Rings of Polycyclic Conjugated Hydrocarbons. 5. Nonalternant Compounds

Abstract: All possible nonalternant hydrocarbons with a total of two, three, or four 5-, 6-, and 7-membered rings have been examined for the partition of their pi-electrons by averaging over all Kekulé structures (considered to contribute equally to the electron distribution) the pi-electrons in each ring in accordance to the rules introduced earlier: for each double bond shared with another ring one pi-electron is taken into account, and for double bonds that are not shared two pi-electrons are added. The trends observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 45 publications
(68 reference statements)
1
35
0
Order By: Relevance
“…In several recent papers, 33,34,[37][38][39][40][41][42][43] an analysis of how π-electrons are shared amongst adjacent rings has led to material conclusions about what have been called "π-electron partitions" or "π-electron content", based on the following conventions: 33,34 (i) in each resonance-structure of the benzenoid ring in question, a shared double-bond is considered to contribute one π-electron to each of the rings that share it;…”
Section: π-Electron Partitions Topological π-Electron Ring-currentsmentioning
confidence: 99%
“…In several recent papers, 33,34,[37][38][39][40][41][42][43] an analysis of how π-electrons are shared amongst adjacent rings has led to material conclusions about what have been called "π-electron partitions" or "π-electron content", based on the following conventions: 33,34 (i) in each resonance-structure of the benzenoid ring in question, a shared double-bond is considered to contribute one π-electron to each of the rings that share it;…”
Section: π-Electron Partitions Topological π-Electron Ring-currentsmentioning
confidence: 99%
“…In connection with [a], note that various applications of Mehtod 1 were discussed in due detail in our earlier papers, especially in (2)(3)(4)6). In the paper (10) it was demonstrated that the π -electron contents of rings, computed by Method 1, are in good agreement with the experimentally observed submolecularly resolved patterns seen in the high-resolution images, obtained by scanning tunneling microscopy.…”
Section: Discussionmentioning
confidence: 60%
“…The partition of π -electrons in the rings of polycyclic conjugated molecules was recently much studied (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). These researches were initiated by two of the present authors (1,2), who proposed a method for assessing the π-electron content of a ring by examining the Kekulé .…”
Section: Introductionmentioning
confidence: 99%
“…If i is odd, then the right-hand side of (28) is positive-valued, implying EC(3) > EC (5), EC(5) > EC (7), etc., proving the validity of (25). If i is even, then the right-hand side of (28) is negative-valued, from which it follows EC(2) < EC (4), EC(4) < EC (6), etc. Thus also the relations (26) are proven.…”
Section: Ec(1) > Ec(2) < Ec(3) > Ec(4) < ··· > Ec(h − 1) < Ec(h)mentioning
confidence: 99%
“…Recently two of the present authors proposed a method for partitioning of π-electrons in rings of polycyclic aromatic compounds [1] and eventually applied it to numerous benzenoid [1,2], coronoid [3], and nonalternant conjugated species [4]. Some general properties of the π-electron contents of rings in benzenoid molecules were also established [5 -8].…”
Section: Introductionmentioning
confidence: 99%